Cost aggregation in export logistics chain - Esa Hämäläinen; Elen Twrdy; Tommi Inkinen (Journal of Open Innovation: Technology, Market, and Complexity, 2017)
This paper analyses cost aggregation in a supply chain. It provides a literature overview on the key concepts of cost aggregation, multimodal transport, logistic chain and maritime transport. The focuses on the value adding process with logistics data and assesses the costs accumulation during the transport process. The paper also reveals multimodal impacts on the logistics costs. The research data is obtained from the costing system of a large export company. The company exports round 90% of its production and mostly to the European markets. The research data contains a sample of 929 invoiced orders to the largest market of the mill. The research results indicate empirical evidence of the cost-function properties. This type of an approach is rare in logistics literature as these detailed data sets are highly difficult to obtain. The article concludes by addressing future research task and directions.
Keywords: 650